The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
All Days 2012
DOI: 10.4043/23353-ms
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Slug Flow in Oil and Gas PIpelines Using a New Transient Simulator

Abstract: LedaFlow ® is a new transient multiphase flow simulator which includes 1D multi-fluid models consisting of mass, momentum and energy conservation equations for each field (continuous, bubble and droplet), as well as compositional tracking. In this paper, a new method called Slug Capturing is employed for slug flow, and the results analyzed and compared with the field data of two different fields. Additionally, for some cases, differences between the new simulator and another commercially available transient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Their presence is usually taken into account through augmentation of friction forces, which must often be adjusted to match real data. Nevertheless, the next generation of flow simulators are expected to include "regime-capturing" approaches which rely on finer grid resolution (Issa & Kempf, 2003;Carneiro et al, 2011;Danielson et al, 2012;Nieckele et al, 2011;Nieckele & Carneiro, 2017). Furthermore, recent developments in experimental investigation of this system (Birvalski et al, 2014(Birvalski et al, , 2015(Birvalski et al, , 2016Ayati et al, 2014Ayati et al, , 2015Ayati et al, , 2016Ayati et al, , 2017André & Bardet, 2017), have shown that the overall bulkflow is strongly coupled with wavy interface.…”
Section: Introductionmentioning
confidence: 99%
“…Their presence is usually taken into account through augmentation of friction forces, which must often be adjusted to match real data. Nevertheless, the next generation of flow simulators are expected to include "regime-capturing" approaches which rely on finer grid resolution (Issa & Kempf, 2003;Carneiro et al, 2011;Danielson et al, 2012;Nieckele et al, 2011;Nieckele & Carneiro, 2017). Furthermore, recent developments in experimental investigation of this system (Birvalski et al, 2014(Birvalski et al, , 2015(Birvalski et al, , 2016Ayati et al, 2014Ayati et al, , 2015Ayati et al, , 2016Ayati et al, , 2017André & Bardet, 2017), have shown that the overall bulkflow is strongly coupled with wavy interface.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is believed to be capable of describing the transition from stratified flow to slug flow, see for instance the work by Issa [16,63] and publications from the commercial simulator LedaFlow [9,64,65]. If the conditions are correct, small instabilities on the gas-liquid interface will become unstable and grow, either to stable waves, or to slugs.…”
Section: Slip Relationsmentioning
confidence: 99%
“…Contrary to slug tracking, the slug capturing method does not need an initial assumed slug distribution and empirical flow regime models as input, and it automatically predicts slug flow regime initiation and development. Many studies describing the slug capturing method and its application and validation for slug flow in horizontal pipelines are present in the literature 9,16‐20 ; it has been demonstrated with these studies that the slug capturing approach is able to capture the slug formation, growth and decay naturally, without introducing special correlations for slug flow, from the numerical solution of the two‐fluid model for stratified flow. In fact, in horizontal pipelines and slightly inclined pipes, it is well known that the slug flow arises from stratified flow because of the growth of hydrodynamic Kelvin‐Helmholtz instabilities: in stratified flow, small perturbations appear on the liquid surface and some of these may grow into larger waves to completely fill the pipe 21 …”
Section: Introductionmentioning
confidence: 99%